Modification of the IDEA (Issue, Discussion, Establish, and Apply) Model to Enhance Learning Effectiveness - Wahyuni, Elvira Sukma; Firdaus, Firdaus; Addi, Mitra Mohd (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2026)
The abrupt transition to online learning led to unprepared implementation and limited instructional control, which significantly reduced students' motivation to learn. This decline in motivation persisted even after returning to in-person classes, contributing to a high failure rate in the Probability and Statistics course. To address this issue, an innovative learning approach is required—one that fosters both motivation and active student participation. The IDEA model (Issue, Discussion, Establish, Apply), a student-centered instructional strategy, was introduced with the aim of improving learning outcomes. Initial implementation of the model led to a notable increase in student pass rates. However, several challenges emerged. While students regained positive habits such as note-taking, group discussions, and teamwork—practices neglected during online learning—they also demonstrated limited independent learning and underutilized supplementary learning resources outside of class. These findings indicate the need for a modified version of the IDEA model that includes mechanisms for monitoring and reflection. Such enhancements would enable both students and lecturers to track progress, identify learning gaps, address challenges proactively, and develop appropriate mitigation strategies to improve overall learning effectiveness.